2010
DOI: 10.1136/bjsm.2010.078725.10
|View full text |Cite
|
Sign up to set email alerts
|

Aromatherapy for sports and fitness

Abstract: The article describes the use of aromatherapy for achieving excellence in sports and fi tness. Aromatherapy is the science of holistic approach for taking care of the body and mind using pleasant smelling of botanical oils. It has been extensively studied and found to be one of the fastest growing areas of alternative medicine. There have been numerous studies showing different plant oils' synergistic effects on body and mind energy facilitating excellence in sports and fi tness. Most of the fi ndings of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They are also shown to improve the body's ability to absorb essential vitamins and nutrients. EO can enter the body through application to the skin, ingestion or inhalation (aromatherapy) [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are also shown to improve the body's ability to absorb essential vitamins and nutrients. EO can enter the body through application to the skin, ingestion or inhalation (aromatherapy) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, EOs can improve anxiety, depression and stimulate neurological function. Other studies have shown that athletes who used peppermint oil before an event had a significant improvement in lung function [4]. When applied to the skin, the EOs are absorbed and the active principles are used by the body for specific therapeutic treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation